(untitled) (Journal of the Bangladesh Association of Young Researchers, 2012)
The purpose of this study is to investigate access and usage of scholarly electronic journals (e-journals) at Dhaka University Library (DUL). It reports the results from a questionnaire-based survey of e-journals access and usages at Dhaka University (DU) serving a variety of academic departments. The survey of the study covers two structured questionnaires comprising of both open- and close-ended questions, and the number of respondents was (N) = 50, 30 faculty members and 20 students. First one was designed for the students of DU in order to gather data and information regarding e-journals access and usage provided by DUL. Second one was structured for the faculty members of DU to explore their expectations, opinions and valuable suggestions with a view to improving e-journal services in DUL. The study identifies some major problems of e-journals access and usage in DUL, and finds out some suitable measures to overcome the problems. The results show a growing interest in e-journals usage among the users at DU. DOI: http://dx.doi.org/10.3329/jbayr.v1i2.10029